2019
DOI: 10.26434/chemrxiv.10067993.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Vitro Blood-Brain-Barrier Permeability and Cytotoxicity of Atorvastatin-Loaded Nanoformulation Against Glioblastoma in 2D and 3D Models

Abstract: Inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase of the family of statins have been suggested as therapeutic options in various tumors. Atorvastatin is a statin with potential to cross the blood-brain-barrier, however, the concentrations necessary for a cytotoxic effect against cancer cells exceeds the concentration achievable via oral administration, which made the development of a novel atorvastatin formulation necessary. We characterized the drug loading and basic physicochemical char… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
(104 reference statements)
3
11
0
Order By: Relevance
“…For better comparison, the 1 H-NMR spectra of the pristine BT44, plain A-pPentOx-A polymer and the (lyophilized) precipitate in chloroform-D (CDCl3) as non-selective solvent (no micelles formation) were obtained (Figure S4). The 1 H-NMR spectra of plain polymer clearly presented all the signals suggesting that polymer existed as unimers in nonaggregated form (Figure S4 green spectra) and it was also evident that the precipitate contained not only the drug but also the hydrophilic polymer (Figure S4 red spectra), corroborating our previous findings [26,43,86]. However, the precipitate was significantly enriched in BT44 compared to the formulation.…”
Section: Physico-chemical Characterization Of Formulationsupporting
confidence: 87%
See 1 more Smart Citation
“…For better comparison, the 1 H-NMR spectra of the pristine BT44, plain A-pPentOx-A polymer and the (lyophilized) precipitate in chloroform-D (CDCl3) as non-selective solvent (no micelles formation) were obtained (Figure S4). The 1 H-NMR spectra of plain polymer clearly presented all the signals suggesting that polymer existed as unimers in nonaggregated form (Figure S4 green spectra) and it was also evident that the precipitate contained not only the drug but also the hydrophilic polymer (Figure S4 red spectra), corroborating our previous findings [26,43,86]. However, the precipitate was significantly enriched in BT44 compared to the formulation.…”
Section: Physico-chemical Characterization Of Formulationsupporting
confidence: 87%
“…Initially the 1 H-NMR spectra of all the three triblock copolymers used in this study were obtained (at concentration of 10 g/L) (Figure S5). while the CUR signals were completely attenuated [43].The 1 H-NMR spectroscopy also revealed a similar pattern for PTX [80] and atorvastatin (ATV) [86] loaded A-pBuOx-A and A-pBuOzi-A ((poly(2-nbutyl-2-oxazine)) micellar formulations, respectively. However, in the absence of drug, small angle neutron scattering (SANS) revealed that the plain A-pBuOzi-A polymer existed as spherical selfassemblies without well-defined core-shell architectures.…”
Section: Physico-chemical Characterization Of Formulationmentioning
confidence: 61%
“…In the present contribution, we have synthesized a thermoresponsive diblock copolymer which is based on thermosensitive pEtOx as hydrophilic (A) and pPrOzi more hydrophobic, yet still thermoresponsive block (B), respectively. As discussed previously, replacing the pMeOx with pEtOx in ABA triblock copolymers, significantly affected (reduced) the drug loading for the same drug [56] while presently, the thermogelling properties of AB diblock copolymer were investigated while exchanging the pMeOx with pEtOx.…”
Section: Synthesis Characterization and Rheologymentioning
confidence: 94%
“…A plethora of studies show the utilization of pMeOx and pEtOx as hydrophilic polymer for the development of hydrogels [26,[45][46][47], electrospun fibres [48], polymer brushes [49], nanoparticles [50], micelles for drug delivery [51][52][53][54][55][56] and for melt electrowriting [57]. Bloksma et al also investigated the thermoresponsive behaviour of few POzi based homopolymers [20].…”
Section: Introductionmentioning
confidence: 99%
“…[70][71] Among the plethora of drug delivery systems for formulation of PTX and CUR, some POx and POzi based formulations stand out for their extraordinary high drug loading capacity and overall solubilisation for PTX and CUR. 43,47,[72][73][74] While CUR is achiral, PTX is chiral with multiple chiral centers but, to the best of our knowledge, does not have a known enantiomer. The formulations were prepared by the thin film hydration method.…”
Section: Formulation Studiesmentioning
confidence: 98%